2015
DOI: 10.1117/12.2082796
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided recognition of dental implants in X-ray images

Abstract: Dental implant recognition in patients without available records is a time-consuming and not straightforward task. The traditional method is a complete user-dependent process, where the expert compares a 2D X-ray image of the dental implant with a generic database. Due to the high number of implants available and the similarity between them, automatic/semi-automatic frameworks to aide implant model detection are essential.In this study, a novel computer-aided framework for dental implant recognition is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The AI models used among the different studies are presented in Table 3. The selected articles were distributed into 3 groups depending on the application of the AI model: implant type recognition (Supplementary Table 1, available online), 13,[27][28][29][30][31][32] models to determine osteointegration success or implant success prediction by using patient risk factors and ontology criteria (Supplementary Table 2, available online), [33][34][35][36][37][38][39] and implant design optimization by combining FEA calculations and AI models (Supplementary Table 2, available online). [40][41][42] The overall accuracy outcome of the AI models developed in the different reviewed studies ranged from 93.8% to 98%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The AI models used among the different studies are presented in Table 3. The selected articles were distributed into 3 groups depending on the application of the AI model: implant type recognition (Supplementary Table 1, available online), 13,[27][28][29][30][31][32] models to determine osteointegration success or implant success prediction by using patient risk factors and ontology criteria (Supplementary Table 2, available online), [33][34][35][36][37][38][39] and implant design optimization by combining FEA calculations and AI models (Supplementary Table 2, available online). [40][41][42] The overall accuracy outcome of the AI models developed in the different reviewed studies ranged from 93.8% to 98%.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42] The overall accuracy outcome of the AI models developed in the different reviewed studies ranged from 93.8% to 98%. 13,[27][28][29][30][31][32] The AI models to predict osteointegration or implant success by using different input data varied among the studies ranging from 62.4% to 80.5%. [33][34][35][36][37][38][39] Finally, the studies that developed AI models to optimize implant designs seem to agree on the applicability of AI models to improve implant designs, minimizing the stress at the implant-bone interface by 36.6% compared with the FEA model, 40 optimizing the implant design porosity, length, and diameter, improving the FEA calculations, 41 or accurately determining the elastic modulus of the implantbone interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Morais et al (2015), a dental implant recognition novel computer-aided framework was suggested. They used this method for a segmentation strategy for semi-automatic implant delineation and a machine learning approach for the recognition of an implant model design.…”
Section: Main Aspect Conclusionmentioning
confidence: 99%